(untitled) (Journal of Medical & Health Sciences Review, 2025)
Chia seed, scientifically termed as Salvia hispanica L., is a good source of omega-3 fatty acids, antioxidants, and dietary fiber all are essential for helping as functional food. The objective of this study was to evaluate the effects of the intake of chia seeds on the lipid profiles and body mass index (BMI) in individuals with high cholesterol. A sample of one hundred District Mardan participants were chosen and divided into two groups, with and without chia seeds, (n=50) and (n=50). Chia seed intake group was supplied with 24 g of chia seeds per day during the month, i.e. three times a week, and no supplementation was provided to the control group. The body size and lipid levels were measured prior to and after an intervention, according to standard rules. Findings displayed critical improvements (p < 0.05) in the chia seeds consumed group in terms of elevated HDL-C and decreased triglycerides (TG), overall cholesterol (TC), in addition to LDL-C and BMI. Mean decreases in BMI of 1.2 kg/m 2 and 1.46 mg/dL (250.19 to 248.73 mg/dL) cholesterol levels. The consumption of chia seeds was tied to improved lifestyle and diet as well. Finally, chia seeds may be a functional food with the ability to assist weight management and decrease cardiovascular risk factors.